Penentuan Kadar Total Flavanoid Pada Ekstrak Etanol Daun Lengkuas Merah (Alpinia purpurata K.Schum) Secara Spektrofotometri Uv-Vis - Mahral Effendi S (Herbal Medicine Journal, 2020)
Galangal leaves contain essential oil of approximately 1% greenish yellow essential oil which mainly consists of 48% methyl-cinnamate, 20% - 30% cineol, eugenol, 1% camphor, sesquiterpen, δ-pinen, galangin. Galangal raw materials can produce essential oil, besides that galangal raw materials are easy to obtain and cheap, so the processing can be developed to obtain an oleoresin product by an extraction process using the MAE (Microwave Assisted Extraction) method so as to produce oleoresin products. This study aims to determine the effect of extraction time using the Microwave Assisted Extraction (MAE) method on total phenolics, flavonoids, tannins, and the antioxidant activity of red galangal oleoresin. The results showed that MAE long treatment had a significant effect (p <0.05) on all observed variables, namely phenolic levels, flavonoid levels, tannin levels and antioxidant activity. The longer the MAE time, the tended to increase the levels of the observed variables, all of the observed variables, namely the flavonoid level 0.6109 mg.QE / g.